Digital-Based Local Tourism Creativity Development Training to Increase Tourist Attraction: Pengabdian - Febrianti; I Wayan Suadnyana; Komang Trigita Juliastari; Komang Shanty Muni Parwati; Firlie Lanovia Amir (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Bali, a global tourism icon, faces significant challenges in distributing tourist visits to local destinations at the rural level due to the digital divide. This community service article aims to describe the implementation of digital-based tourism creativity development training for local destination managers in Bali to increase their attractiveness and competitiveness. The main problems identified among partners (Pokdarwis in Bali) were reliance on traditional marketing and the low quality of digital content capable of representing the uniqueness of local culture and nature. The community service method was carried out using an Asset-Based Community Development (ABCD) approach, which included visual content creation workshops, cultural narrative-based copywriting training ( storytelling ), and social media algorithm optimization. The community service results showed a significant increase in participants' creative capacity in producing aesthetic and informative content, as well as increased interaction on partner destinations' social media channels. The conclusion of this activity emphasizes that the digitalization of local tourism in Bali must be rooted in the creative packaging of local wisdom, so as to attract quality tourist segments and support the sustainable recovery of the creative economy post-pandemic.